Peningkatan Kualitas Sumber Daya Manusia di Rumah Atsiri Indonesia Melalui Penyusunan Modul Pelatihan Bilingual: Improving the Quality of Human Resources in Rumah Atsiri Indonesia through Bilingual Training Module Arrangement - Wulandari, Desi; Denistia, Karlina; Yuda, Jotika; Perwira, Yanuarria; Sari, Intan; Inderajati, Aal; Priyanto, Agus (Politeknik Negeri Jember, 2024)
Rumah Atsiri Indonesia (RAI) as a tourist destination that carries the concept of integrated destination, has a mission to educate the public about the history of essential oils and essential plants that can be used for various purposes. In an effort to provide this information to all visitors, RAI is committed to providing comprehensive information to all visitors, both local and foreign tourists. The increasing number of foreign tourists requires RAI's human resources, especially educators, to improve their competence in English. The Community Service Programme (PKM) carried out by the English for Creative Industries Research Group from the D-3 English Study Programme, Vocational School, UNS, with the title Improving the Quality of Human Resources at Rumah Atsiri Indonesia through Bilingual Training Modules Arrangement, is expected to be a solution to this problem. This PKM activity is carried out in several stages of work: first, the analysis of partner needs; second, the process of translating existing modules into English; third, the arrangements of modules in two languages; and last, the overall program evaluation. The translation process refers to the stages of translation by Nida and Taber, as well as translation techniques by Molina and Albir. The results of the translation are then compiled in the form of bilingual modules that can be studied independently by RAI’s human resources. keywords: module, bilingual, translation